2017
DOI: 10.1039/c7cp05211a
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the photoinduced electron transfer and binding modes of a pyrene–porphyrin dyad to DNA

Abstract: The binding modes of a pyrene-porphyrin dyad, (1-pyrenyl)-tris(N-methyl-p-pyridino)porphyrin (PyTMpyP), to DNA and its photophysical properties have been investigated using various spectroscopic techniques. The circular dichroism (CD) spectrum of PyTMpyP bound to DNA (PyTMpyP-DNA) showed one negative and two positive bands in the Soret region. The CD signal in the pyrene absorption region was positive. The shape of the CD spectrum does not support an intercalative binding mode of TMpyP, which would typically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…[ 40 ] The faint signal of D + D' at 2970 cm −1 corresponds to the combination mode of the D and D' modes. The confirmation of I D / I G >1 and I 2D / I G <1 indicates the existence of vacancy‐type defects, [ 41 ] a finding consistent with the observation in TEM images. In addition, the FTIR spectra of V 2 O 5 and V 2 O 5 @LIG indicate a redshift of the peaks due to the strong interaction of LIG with V 2 O 5 (Figure S9, Supporting Information).…”
Section: Resultssupporting
confidence: 80%
“…[ 40 ] The faint signal of D + D' at 2970 cm −1 corresponds to the combination mode of the D and D' modes. The confirmation of I D / I G >1 and I 2D / I G <1 indicates the existence of vacancy‐type defects, [ 41 ] a finding consistent with the observation in TEM images. In addition, the FTIR spectra of V 2 O 5 and V 2 O 5 @LIG indicate a redshift of the peaks due to the strong interaction of LIG with V 2 O 5 (Figure S9, Supporting Information).…”
Section: Resultssupporting
confidence: 80%
“…Design of new chromophores that are capable of harvesting sunlight in the low-energy visible and near-infrared (NIR) spectral envelopes attracted a lot of attention in recent decades because of the potential use of such systems in organic- and dye-sensitized solar cells. In addition, the ability to facilitate relatively strong noncovalent interactions between such chromophores and nanocarbon-based electron-accepting materials (fullerenes, nanotubes, and graphene) is thought to be advantageous in the processing of high-efficiency organic bulk heterojunction solar cells. To achieve this goal, many porphyrins, subphthalocyanines, and boron-dipyrromethenes (BODIPYs) were functionalized with a variety of electron-donating groups that improve donor–acceptor (D–A) interactions between extended π-systems. Alternatively, the introduction of the polyaromatic fragments that are either conjugated or not conjugated into chromophores’ π-system can also improve noncovalent interactions in these D–A assemblies. Covalently bound pyrene was shown to facilitate noncovalent interactions with carbon nanotubes and graphene. It has also been shown that when pyrene fragments are decoupled from the chromophores’ π-system, this extended aromatic group can facilitate an unwanted pyrene-to-chromophore electron-transfer process as well as the formation of a chromophore-centered triplet state. We have recently demonstrat...…”
Section: Introductionmentioning
confidence: 99%
“…Within this framework, the rate constants for charge separation and recombination may be expressed as where where ℏ = h /2π ( h is Planck’s constant), k B is the Boltzmann constant, T is the temperature (296 K), H DA is the electronic coupling matrix element, S c is the Huang–Rhys factor, Δ G is the free-energy change, λ i is the nuclear reorganization energy, and ⟨ω c ⟩ is the average high-frequency vibrational frequency. A value of ℏ⟨ω c ⟩ = 1500 cm –1 could be assumed for ET processes involving aromatic molecules. , λ s is the solvent reorganization energy, which is expressed as where ε 0 is the vacuum permittivity, r D (3.0 Å for guanine) and r A (9.2 Å for porphyrin) are the ionic radii of the donor and acceptor, respectively, r DA (= r D + r A ) is the donor–acceptor separation, n (=1.332) is the solvent refractive index, and ε s (=81) is the static dielectric constant of the solvent. Therefore, the value of λ s has been estimated to be ∼1.10 eV. The values of λ i and H DA can be estimated as ∼0.37 eV and ∼193.5 cm–1, respectively, according to formula 1 by using the experimental results of k b,exp (=1/τ G , see Table ) data of H 2 TMPyP-dGMP and PdTMPyP-dGMP, which are consistent with the earlier reports. ,, Then, the dependence of k values on the driving force (−Δ G ) can be displayed in Figure .…”
Section: Resultsmentioning
confidence: 99%